Who "belongs"? - Bajt, Veronika (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2016)
Setting nationalism and national identity in the theoretical framework of migration, the paper asserts that nation-states remain in strong control over who belongs and who is categorised as a foreigner. The nationalising effects of state policies perpetuate the embeddedness of membership in the exclusionary community of the nation rather than effectively promulgating enactments of inclusive civic state membership. Drawing on the chosen example of Slovenia as a relatively new nation-state and a recent country of immigration, the paper offers new insights into migrant experiences as illustrations of the need to relegate to the dustbin of history the existing practices of preferential treatment for members of the dominant nation. Arguing that it is essential to study migration in conjunction with nationalism, the paper urges a more inclusive theoretical perspective which would take account of migrants.
Keywords: nacionalizem; nationalism; migration; human migration; migracije; nacionalne države; nation-state; national identity; nacionalna identiteta; migrant integration; integracija migrantov; pripadnost; belonging; Slovenia; Slovenija; state; država; narod; people; nacija; državljanstvo; državna politika; narodna identiteta; narodna kultura; nacionalna kultura; državljani; migranti; tujci; imigracija; integracija